1966
DOI: 10.1083/jcb.30.2.333
|View full text |Cite
|
Sign up to set email alerts
|

THE FINE STRUCTURE OF THE EXOERYTHROCYTIC STAGES OF PLASMODIUM FALLAX

Abstract: The fine structure of the exoerythrocytic cycle of an avian malarial parasite, Plasmodium fallax, has been analyzed using preparations grown in a tissue culture system derived from embryonic turkey brain cells which were fixed in glutaraldehyde-OsO4. The mature merozoite, an elongated cell 3-to 4-/~ long and l-to 2-# wide, is ensheathed in a complex doublelayered pellicle. The anterior end consists of a conoid, from which emanate two lobed paired organelles and several closely associated dense bodies. A nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 28 publications
4
57
0
Order By: Relevance
“…4B). After growth and multiple nuclear divisions, polarized parasites are regenerated when the nuclei move to the schizont periphery and associate with the assembling IMC, subpellicular microtubules, and apical organelles (3,12,72,157) round shape and lack of apical specialization, replicating parasites are noninvasive during schizogeny. P. falciparum replication has been studied by observing microtubule structures during replication in red cells (130).…”
Section: Role In Apicomplexan Replicationmentioning
confidence: 99%
See 2 more Smart Citations
“…4B). After growth and multiple nuclear divisions, polarized parasites are regenerated when the nuclei move to the schizont periphery and associate with the assembling IMC, subpellicular microtubules, and apical organelles (3,12,72,157) round shape and lack of apical specialization, replicating parasites are noninvasive during schizogeny. P. falciparum replication has been studied by observing microtubule structures during replication in red cells (130).…”
Section: Role In Apicomplexan Replicationmentioning
confidence: 99%
“…Subpellicular microtubules confer both elongated shape and apical polarity to apicomplexan parasites. Replicative forms or drug-treated parasites that lack subpellicular microtubules are nonpolar, nonmotile, and noninvasive (72,168). Subpellicular microtubules are organized by lateral association with the apical polar ring (APR), a circular MTOC (120,134).…”
Section: Microtubules In the Apicomplexa Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA circle was localized in situ to a multimembranous structure, previously described as a 'spherical body' (e.g. Hepler et al, 1966) or a 'multimembranous vesicle' (e.g. Schrével, 1971), identified recently as a secondary vestigial plastid, and coined the term apicoplast (McFadden et al, 1997;Köhler et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Scheme I, as based on The search for the presence of coenzyme Qn in species of Plasmodium was successful, and mass spectral data and reversed-phase chromatographic results of Rietz et al (6) showed the presence of coenzyme Qs in P. lophurae. Vitamin (10) and Rudzinska and Trager (11) and the dependence of the parasite upon a gas phase containing a given concentration of oxygen are known; Anfinsen et al (12). Drugs General Procedure for 7-Alkylmercapto-6-hydroxy-5,8-quinolinequinones.…”
mentioning
confidence: 99%